An Experience of Using the GQM Approach in a Remote Environment to Define Requirements Metrics - Carvalho, Rainara Maia; Marques, Anna Beatriz; Andrade, Rossana; Sousa, Amanda; Dias, Raquel; Campagnoli, Guilherme (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
It is well known that many problems in software development arise because the software requirements area is neglected. In this way, the quality of requirements is essential to guarantee the acceptance of the software and, thus, the success of the project. Software metrics can be used to assess the quality of products and artifacts. The literature has several metrics for the requirements area. However, to better meet the particularities of a project, the ideal is to define specific metrics. The Goal-Question-Metric (GQM) is an approach for defining metrics oriented to the organization’s goals. This paper aims to present an experience report about applying the GQM approach to define requirements metrics in a software project in the industry. Since we are going through a pandemic, we adopted GQM in the context of remote work. This paper presents the adaptations that were made, as well as the lessons learned about the application of GQM in a remote environment.